The genetics and breeding of the Portuguese oyster, Crassostrea angulata: lessons, experiences, and challenges in Vietnam - Le, Thi Nhu Phuong; Vu, Sang Van; Ugalde, Sarah C.; Subramanian, Sankar; Gilmour, Arthur; Dove, Michael; Vu, In Van; Geist, Juergen; Tran, Thi Nang Thu; Gondro, Cedric; Cao, Giang Truong; Le, Tat Thanh; et al. (Frontiers in Marine Science, 2023)
Aquaculture mollusc production is predominantly from Asia, with more than 80% of the total biomass produced in China. Vietnam's annual mollusc production is around 190,000 t, which is comparatively small given its coastal resources. A significant challenge for mollusc production, and oysters in particular, is the supply of high-quality spat. Most mollusc spat in Vietnam comes from local wild sources or are imported from China. Particularly in the case of oysters, importation of oyster spat into Vietnam from other jurisdictions is not controlled, unreliable and presents a biosecurity risk to the industry. Control of the complete life cycle in hatcheries can increase the sustainability and reliability of spat supply with the advantages of independence from the wild and genetic enhancement in the long-term. Beyond wellestablished selection methods based on phenotypic data for pedigreed families, the rapid development of genomic technology has enabled to innovate hatchery technologies based on genetic programs. This technology allows greater insight into oyster genetics in intensive aquaculture production systems. Recent reviews of selection programs demonstrate that inbreeding control via mate selection is an effective strategy for oyster species. Genetic response through combinations of individual and family-based selection can enhance morphometric traits by 10% per generation and disease resistance by 15% per generation in many aquaculture species. Genomic techniques provide information for selecting candidates at an earlier stage and improving prediction accuracy. In this paper, we review the literature on popular genomic tools and breeding techniques used for molluscs, focusing on the Portuguese oyster, Crassostrea angulata. This is to better comprehend how modern quantitative and molecular genetic technologies are being applied in mollusc breeding programs. It considers opportunities for and the feasibility of using genomic-based selection as well as the challenges that are faced in breeding programs transitioning to these new methods.